Catalyst modification strategies to enhance the catalyst activity and stability during steam reforming of acetic acid for hydrogen production. (21st May 2019) - Kumar, Ankit; Singh, Rupesh; Sinha, A.S.K.
Abstract: A high energy content (∼122 MJ/kg H2 ) and presence of hydrogen-bearing compounds abundance in nature make hydrogen forth runner candidate to fulfill future energy requirements. Biomass being abundant and carbon neutral is one of the promising source of hydrogen production. In addition, it also addresses agricultural waste disposal problems and will bring down our dependency on fossil fuel for energy requirements. Biomass-derived bio-oil can be an efficient way for hydrogen production. Acetic acid is the major component of bio-oil and has been extensively studied by the researchers round the globe as a test component of bio-oil for hydrogen generation. Hydrogen can be generated from acetic acid via catalytic steam reforming process which is thermodynamically feasible. A number of nickel-based catalysts have been reported. However, the coke deposition during reforming remains a major challenge. In this review, we have investigated all possible reactions during acetic acid steam reforming (AASR), which can cause coke deposition over the catalyst surface. Different operating parameters such as temperature and steam to carbon feed ratio affect not only the product distribution but also the carbon formation during the reaction. Present review elaborates effects of preparation methods, active metal catalyst including bimetallic catalysts, type of support and microstructure of catalysts on coke resistance behavior and catalyst stability during reforming reactions. The present study also focuses on the effects of a combination of a variety of alkali and alkaline earth metals (AAEM) promoters on coke deposition. Effect of specially designed reactors and the addition of oxygen on carbon deposition during AASR have also been analyzed. This review based on the available literature focuses mainly on the catalyst deactivation because of coke deposition, and possible strategies to minimize catalyst deactivation during AASR. Highlights: Discuss the production of hydrogen from biomass derived acetic acid and detailed mechanism of coke deposition. This review consider all the possible way to minimize the coke deposition during the AcOH steam reforming. The detail discussion of correlation of operating parameters with carbon generation. The contributions of different active metal and support material are also discussed to reduce coke deposition. Catalyst deactivation via active metal sintering also discussed briefly.